The new economics of outdoor recreation - Shaw, W. Douglass; Hanley, Nick.; Wright, Robert E., 1958- (Cheltenham, Glos., UK ; Northhampton, Mass. : E. Elgar, 2003)
This innovative book presents a series of up-to-date analyses of the economics of outdoor recreation. The distinguished group of authors covers real-world recreation management issues and applies economic understanding to these problems. An extensive introduction by the editors details the historical background of economists interests in this subject, and reveals how economics can provide practical insights into improving how we manage our natural recreation areas. The book is divided into three parts, each of which focuses on a specific environmental resource: mountains, forests, and rivers and the sea. An array of valuation methods including stated preference and revealed preference techniques are then applied to various outdoor recreation activities which occur in these different settings. These include such diverse pursuits as rock climbing, skiing, fishing, hunting and whale watching. The authors clearly demonstrate how recreation modelling can offer a productive link between people (their preferences and behaviour) and the natural environment.
Includes bibliographical references and index.
lje 29/01/14
Loans
Keywords: Outdoor recreation -- Environmental aspects; Outdoor recreation -- Economic aspects; Econometrics